Fiber length, thermal, mechanical, and dynamic mechanical properties of injection-molded glass-fiber/polyamide 6,6: Plasticization effect - Hassan, A.; Salleh, N.M.; Yahya, R.; Sheikh, M.R.K. (2011)
Unreinforced- and glass fiber-reinforced-polyamide 6,6 specimens were subjected to dry, 50 RH, and wet conditions. FLD study showed that more fiber degradation occurred during processing of the composites with higher fiber loading. TGA results revealed that about 2 and 5 levels of moisture have been absorbed by the specimens subjected to 50 RH and wet conditions, respectively. From DSC results, with moisture uptake, there were no significance changes in the melting temperature, crystallization temperature, and enthalpy of crystalline; however, degree of crystallinity and enthalpy of melting decreased. Tensile strength, tensile modulus, flexural strength, and flexural modulus decreased with moisture uptake, while tensile strain and flexural displacement increased. DMA study showed that tan delta at room temperature and tan delta maxima increased with moisture absorption, while temperatures at maximum tan delta in Î±-and Î²-transition regions decreased.